2009
DOI: 10.1007/s12237-009-9207-3
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton as an Indicator of Improving Water Quality in the Golden Horn Estuary

Abstract: The variation in phytoplankton community as a response to improving water quality has been studied in the severely polluted Golden Horn Estuary (GHE). Phytoplankton data collected monthly for 4 years and a detailed set of environmental parameters clearly showed the remarkable change in the GHE. The GHE ecosystem did not respond to numerous rehabilitation efforts to improve water quality, unless strict measures were taken to enhance water circulation. The opening of a bridge operating on large buoys and release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
53
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 21 publications
8
53
3
Order By: Relevance
“…Dinoflagellates showed a wider distribution throughout the study area than diatoms. The third group, including all phytoflagellates, played an important role particularly in the upper part of the estuary, as reported in an earlier work (Tas et al, 2009). A wide distribution and high abundances of mixotrophic flagellates in the upper estuary indicates the suitability of trophic conditions for mixotrophy.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Dinoflagellates showed a wider distribution throughout the study area than diatoms. The third group, including all phytoflagellates, played an important role particularly in the upper part of the estuary, as reported in an earlier work (Tas et al, 2009). A wide distribution and high abundances of mixotrophic flagellates in the upper estuary indicates the suitability of trophic conditions for mixotrophy.…”
Section: Discussionsupporting
confidence: 70%
“…Considering the seasonality of different harmful species, it appears that spring and summer poses a higher risk for the occurrence of harmful conditions , as reported in previous studies at the region (Tas et al, 2009) and elsewhere (Zingone et al, 2006). Moreover, water discolorations caused by mostly different dinoflagellates and phytoflagellates, were observed in spring and summer depending on the water column stability.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…The previous studies on phytoplankton carried out in this study area, when it was extremely polluted, demonstrated that phytoplankton abundance was very low and even they were absent particularly at the upper estuary (Uysal and Unsal, 1996;Tas and Okus, 2003;Tas et al 2009). During rehabilitation of the GHE (after 2000), phytoplankton abundance increased and dense blooms of phytoplankton occurred in spring and summer Tas and Okus, 2011;Tas, 2015).…”
Section: Introductionmentioning
confidence: 65%